IMPLEMENTASI TEKNIK MENGAJAR BERBICARA: PENDEKATAN WAWANCARA PADA PEMBELAJAR BIPA MANDIRI (LEVEL 1) - Tanti, Septiana (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2024)
This research aims to evaluate the implementation of speaking teaching techniques using an interview approach to independent learners. Through interview techniques, this research focuses on developing learners' speaking skills by paying attention to Graduate Competency Standards (SKL). Data was collected through observation, interviews and analysis of audio recordings. The subject in this research is an independent learner where the subject of this research is the main informant. This research uses a qualitative descriptive method by describing the importance of applying speaking teaching techniques using an interview approach. The results show that, although students are able to answer questions with adequate understanding, there is still a tendency to use English vocabulary and a low level of confidence in expressing ideas. Therefore, the implementation of interview techniques needs to be accompanied by additional learning strategies that overcome these shortcomings, such as strengthening vocabulary and developing self-confidence. This research provides important insights for improving the effectiveness of speaking teaching in the BIPA level 1 context.